Intrinsic vascular dopamine – a key modulator of hypoxia‐induced vasodilatation in splanchnic vessels. (10th March 2014) - Pfeil, Uwe; Kuncova, Jitka; Brüggmann, Doerthe; Paddenberg, Renate; Rafiq, Amir; Henrich, Michael; Weigand, Markus A.; Schlüter, Klaus‐Dieter; Mewe, Marco; Middendorff, Ralf; Slavikova, Jana; Kummer, Wolfgang
Abstract : Key points: Dopamine is a member of the catecholamine family and a precursor in the biosynthetic pathway of adrenaline and noradrenaline, which acts as an independent neurotransmitter in the sympathetic nervous system and as a paracrine hormone. We found that the arterial wall of systemic vessels itself, i.e. the endothelial cells and the underlying tissue, produces a substantial pool of dopamine. This intrinsic vascular dopamine is released upon stimulation by decreasing oxygen concentrations, causing a dilatation of the blood vessel, thereby increasing blood flow and subsequently oxygenation of the tissue. This study identifies dopamine as a novel non‐neuronal intrinsic vasodilator in the arterial wall, crucially involved in P O 2 ‐driven modulation of vascular tone and maintenance of tissue oxygenation under conditions where reduced oxygen supply may cause severe damage to body systems as in stroke, heart infarction and pulmonary hypertension. Abstract: Dopamine not only is a precursor of the catecholamines noradrenaline and adrenaline but also serves as an independent neurotransmitter and paracrine hormone. It plays an important role in the pathogenesis of hypertension and is a potent vasodilator in many mammalian systemic arteries, strongly suggesting an endogenous source of dopamine in the vascular wall. Here we demonstrated dopamine, noradrenaline and adrenaline in rat aorta and superior mesenteric arteries (SMA) by radioimmunoassay. Chemical sympathectomy with 6‐hydroxydopamine showed a significant reduction of noradrenaline and adrenaline, while dopamine levels remained unaffected. Isolated endothelial cells were able to synthesize and release dopamine upon cAMP stimulation. Consistent with these data, mRNAs coding for catecholamine synthesizing enzymes, i.e. tyrosine hydroxylase (TH), aromaticl ‐amino acid decarboxylase, and dopamine‐β‐hydroxylase were detected by RT‐PCR in cultured endothelial cells from SMA. TH protein was detected by immunohistochemisty and Western blot. Exposure of endothelial cells to hypoxia (1% O2 ) increased TH mRNA. Vascular smooth muscle cells partially expressed catecholaminergic traits. A physiological role of endogenous vascular dopamine was shown in SMA, where D1 dopamine receptor blockade abrogated hypoxic vasodilatation. Experiments on SMA with endothelial denudation revealed a significant contribution of the endothelium, although subendothelial dopamine release dominated. From these results we conclude that endothelial cells and cells of the underlying vascular wall synthesize and release dopamine in an oxygen‐regulated manner. In the splanchnic vasculature, this intrinsic non‐neuronal dopamine is the dominating vasodilator released upon lowering of oxygen tension.